2016
DOI: 10.1097/shk.0000000000000673
|View full text |Cite
|
Sign up to set email alerts
|

Association of Heart Rate with N-Terminal Pro-B-Type Natriuretic Peptide in Septic Patients

Abstract: Tachycardia was significantly and independently associated with NT-proBNP elevation and lower survival rate in septic patients, although no association was observed in nonseptic patients. Increased NT-proBNP in sepsis with tachycardia might predict poor outcomes in ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…However, in the same experimental study, it was also found that, in contrast to β-blockers, isolated reduction in heart rate by ivabradine did not induce any change in the most commonly assessed inflammatory pathways in rats with septic shock [14]. Thus, it could be argued that the correction of elevated heart rate, even if crucial (particularly when tachycardia is prolonged in time), is not the only expected endpoint with the prescription of β1-blockers during septic shock [22].…”
Section: Modulation Of Inflammation By Low Doses Of Esmololmentioning
confidence: 89%
“…However, in the same experimental study, it was also found that, in contrast to β-blockers, isolated reduction in heart rate by ivabradine did not induce any change in the most commonly assessed inflammatory pathways in rats with septic shock [14]. Thus, it could be argued that the correction of elevated heart rate, even if crucial (particularly when tachycardia is prolonged in time), is not the only expected endpoint with the prescription of β1-blockers during septic shock [22].…”
Section: Modulation Of Inflammation By Low Doses Of Esmololmentioning
confidence: 89%
“…The absence of elevated troponin levels suggests that myocardial injury was also not a hallmark. However, elevation in BNP at this timepoint is indicative of myocardial dysfunction and mirrors clinical findings in patients with established sepsis, particularly in those with a poor prognosis [ 32 35 ]. This finding implies heart failure may be an important mechanism underlying death.…”
Section: Discussionmentioning
confidence: 99%
“…A dysregulated response alters vital signs such as body temperature (BT), heart rate (HR), blood pressure (BP), and respiratory rate (RR) [3,4]. Alterations such as hypothermia, fever, tachycardia, hypotension, or tachypnea tend to be associated with altered clinical outcomes [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%